Effects Of Human Umbilical Cord-Derived Mesenchymal Stem Cells On Human Corneal Epithelial Cells’ Growth - Azmi, Siti Maisura (2019)
Ex vivo cultivated corneal limbal stem cell (LSC) transplantation is the contemporary therapy for comeal epithelial regeneration. The success rate of this therapy is dependent on the cell culture conditions and the carrier system. Human umbilical cord mesenchymal stem cells (hUC-MSCs) has regenerative ability and are rich with paracrine factors. Cells cultivated in spherical scaffolds could provide a similar in vivo environment to the cell niche and may positively alter the stem cells properties. This study aims to improve the cellular quality of the comeal epithelial transplantation graft using a robust cell population method. Human telomere modified comeal epithelial cells (hTCECs) were co-cultured in direct and indirect cell culture with hUC-MSCs. Characterisation of corneal markers p63, ABCG2, ABCB5, and differentiation marker K3 were performed.